Effect of Temperature on Growth of Salmonella in Rehydrated Skim Milk from a Food-Poisoning Outbreak - Julseth, R. M. (1969)
Low numbers of salmonellae in a dried skim milk sample that was implicated in an outbreak of salmonellosis grew rapidly upon rehydration and incubation.